Management Strategy Of Tiktok To Build Brand Awareness In Bkkbn Program Of Bali Province - Ni Made Satyawati; Kadek Devi Kalfika Anggria Wardani; Anak Agung Ngurah Eddy Supriyadinata Gorda (Universitas Serang Raya, 2023)
Social media is a digital platform that facilitates communicating with each other, sharing videos, information, potos with each user. Social media is very useful for companies in increasing brand awareness because with social media, companies will find it easier to connect with the public or the intended target. The Bali Province BKKBN also uses social media, one of which is Tiktok. BKKBN Province Bali also uses social media, one of which is Tiktok. The main problems faced by the company are the lack of human resources that focus on managing tiktok social media and the lack of planning strategies to maximize video content uploaded on tiktok @bkkbnbali. The purpose of this community service is to improve the quality of human resources and to know the social media management strategy to build brand awareness. Data were collected through observation, interviews, documentation, and literature from several related journals. The results of the planning strategy in this study indicate that good Tiktok social media management will affect a company's brand awareness.